2016
DOI: 10.1002/ece3.2275
|View full text |Cite
|
Sign up to set email alerts
|

Variation of life‐history traits of the Asian corn borer, Ostrinia furnacalis in relation to temperature and geographical latitude

Abstract: Life‐history traits from four geographical populations (tropical Ledong population [LD], subtropical Guangzhou [GZ] and Yongxiu populations, and temperate Langfang population [LF]) of the Asian corn borer, Ostrinia furnacalis were investigated at a wide range of temperatures (20–32°C). The larval and pupal times were significantly decreased with increasing rearing temperature, and growth rate was positively correlated with temperature. The relationship between body weight and rearing temperature in O. furnacal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 71 publications
(127 reference statements)
4
17
0
Order By: Relevance
“…To summarize, we documented strong latitudinal differentiation in larval growth rate and in adult lifespan, with longer lifespans in the faster growing low‐latitude populations. Our study complements several other common garden studies with insects reporting latitudinal variation in adult lifespan (Schmidt et al , Munch and Salinas , Xiao et al , Debecker et al , Durmaz et al ), yet the mechanistic basis for the reported patterns are typically unknown. Notably, Hong and Shurin (), showed that the faster growing high‐latitude populations of a copepod suffered a reduced lifespan compared to the slower growing low‐latitude populations.…”
Section: Discussionsupporting
confidence: 75%
“…To summarize, we documented strong latitudinal differentiation in larval growth rate and in adult lifespan, with longer lifespans in the faster growing low‐latitude populations. Our study complements several other common garden studies with insects reporting latitudinal variation in adult lifespan (Schmidt et al , Munch and Salinas , Xiao et al , Debecker et al , Durmaz et al ), yet the mechanistic basis for the reported patterns are typically unknown. Notably, Hong and Shurin (), showed that the faster growing high‐latitude populations of a copepod suffered a reduced lifespan compared to the slower growing low‐latitude populations.…”
Section: Discussionsupporting
confidence: 75%
“…However, increasing evidence has shown that the reverse TSR in insects is also common. For example, reversals of the TSR have been found in four species of mayfly (Atkinson, ); four species of British grasshoppers (Willott & Hassall, ); the tropical butterfly, Bicyclus anynana (Fischer, Bot, & Brakefield, ); the small cabbage white, butterfly, Pieris rapae (Kingsolver, Massie, Ragland, & Smith, ); the Asian corn borer, Ostrinia furnacalis (He, Tang, Huang, Gao, & Xue, ; Xiao et al, ); and the rice stem borer, Chilo suppressalis (Fu, He, Zhou, Xiao, & Xue, ; Huang, Xiao, He, & Xue, ). As such, why do some insect species follow the TSR and some exhibit the reverse TSR?…”
Section: Discussionmentioning
confidence: 99%
“…Those species with summer diapause may exhibit the TSR, as indicated by the cabbage beetle, C. bowringi (Tang, He, Chen, Fu, & Xue, ) and this butterfly, P. melete because their reproductive periods occur in the spring and autumn and because these insects have experienced strong selection for body size under relatively low environmental temperatures during the process of evolution. Those species with winter diapause triggered by shortening day lengths combined with high autumn temperatures may exhibit the reverse TSR, as indicated by the Asian corn borer, O. furnacalis (He et al, ; Xiao et al, ), and the rice stem borer, C. suppressalis (Fu et al, ; Huang et al, ). These two species enter winter diapause in response to high autumn temperatures and experience strong selection for body size under warm conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations